(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
This article arises in the development of the author’s doctoral thesis and his practice as a basic secondary education teacher in a public school in Bogotá, Colombia. The article presents the main elements of a curricular proposal that articulates radical political education and recent history. To do this, it initially addresses the opinion of Latin Americans about democracy as a form of government and points out the growing support for authoritarian political systems. Subsequently, he proposes the conception of radical political education from which the present curricular proposal is developed, in the context of the trends around political education in Colombia. Then, he proposes a series of possible connections between the perspective of recent history and radical political education, to finally describe the elements of a curricular proposal that articulates radical political education and recent history.